HLA-B35, a common genetic trait, in a familial case of Henoch-Schoenlein purpura and Berger's disease. - Pellegrin, M C; Matarazzo, L; Neri, E; Pennesi, M; Crovella, S (Genet Mol Res, 2014)
Nephritis characterized by IgA mesangial depositions has been described both in Henoch-Schoenlein purpura (HSP) and in Berger's disease (BD), but common genetic traits are still uncertain. We report here the case of two brothers, the first affected by HSP with persistent nephritis and the second by BD, accidentally discovered as silent microhematuria 1 year after HSP onset in the first brother. HLA genotyping demonstrated the presence of HLA-B35 in both patients. Our findings reinforce the need to screen for urinary abnormalities in family members of patients affected by HSP nephritis to identify a silent IgA nephropathy.
Keywords: Adolescent; Child; Female; Genotype; Glomerulonephritis, IGA; HLA-B35 Antigen; Humans; Male; Middle Aged; Nephritis; Phenotype; Purpura, Schoenlein-Henoch